PARADOKS PENOKOHAN DALAM SASTRA DAKWAH WALISONGO: PALGUNADI SEBAGAI ANTITESA SISI GELAP ARJUNA DAN SIMBOLISME TERHADAP KONSEP TAWAZUN - Hidayatullah, Ahmad (IAIN Padangsidimpuan, 2023)
Wayang as a complex work of art in which there is Da'wah nuanced literature, does have a peculiarity in its composition, both in terms of character development and storyline. This was done to adjust the wayang, which was mostly adopted from the Hindu epic Ramayana-Mahabharata to suit Islamic values. One of them is by including a paradox that is full of balance values (tawazun) in the characterization of Arjuna (Palguna)-Bambang Ekalaya (Palgunadi). Using a type of qualitative research that is library research with a structuralism analysis approach, this article tries to explore how the paradox of characterizations is carried out in da'wah literature, in this case the construction of the Palgunadi story as an antithesis to Arjuna's dark side and its symbolism to the concept of tawazun. The results of this study can be found that there are three aspects of balance that are found from the symbolization of the Arjuna-Palgunadi paradox, including; First, balance in life; Second, the balance of opportunities in seeking knowledge; Third, balance in looking at social status.